High Dietary Niche Overlap Between Non-native and Native Ant Species in Natural Ecosystems. Issue 1 (3rd December 2020) - Probert, Anna F; Ward, Darren F; Beggs, Jacqueline R; Bury, Sarah J; Hermans, Syrie M; Lear, Gavin; Stanley, Margaret C
Abstract: Ants represent a highly diverse and ecologically important group of insects found in almost all terrestrial ecosystems. A subset of ant species have been widely transported around the globe and invade many natural ecosystems, often out-competing native counterparts and causing varying impacts on recipient ecosystems. Decisions to control non-native ant populations require an understanding of their interactions and related impacts on native communities. We employed stable isotope analysis and metabarcoding techniques to identify potential dietary niche overlap and identify gut contents of 10 ant species found in natural ecosystems in Aotearoa New Zealand. Additionally, we looked at co-occurrence to identify potential competitive interactions among native and non-native ant species. Ants fed mainly across two trophic levels, with high dietary overlap. Relative to other ant species sampled, two non-native ant species, Linepithema humile and Technomyrmex jocosus, were found to feed at the lowest trophic level. The largest isotopic niche overlap was observed between the native Monomorium antarcticum and the invasive Ochetellus glaber, with analyses revealing a negative co-occurrence pattern. Sequence data of ant gut content identified 51 molecular operational taxonomic units, representing 22 orders and 34 families, and primarily consisting of arthropod DNA. Although we generally found high dietary overlap among species, negative occurrence between a dominant, non-native species and a ubiquitous native species indicates that species-specific interactions could be negatively impacting native ecosystems. Our research progresses and informs the currently limited knowledge around establishing protocols for metabarcoding to investigate ant diet and interactions between native and non-native ant species.